TECHNIQUES OF TRANSLATING THESIS ABSTRACTS OF ECONOMICS DEPARTMENT STUDENTS IN MEDAN STATE UNIVERSITY - Sofyan Fernandes Hutauruk; Masitowarni Siregar (State University of Medan, 2015)
The study deals with the techniques of translation on thesis abstracts inEconomics Department. The objectives of study were to identify the types oftranslation techniques, to find out the most dominant type of translationtechniques used, and to describe the reasons of the translation techniques used intranslating thesis abstract. The study used descriptive qualitative design.Nazir(1998: 34) states that descriptive qualitative is a method of research thatmakes the description of the situation of events or occurrences clearer. It isunderstood that descriptive qualitative is a method of research which provides thedescription of situation, events or occurrences, so this method is an intention toaccumulate the basic data. Qualitative research involves analysis of data such aswords and phrases written in abstracts. The data were taken from twentytranslated thesis abstracts of Economic Department. The findings show that therewere eight techniques of eighteen techniques used in thesis abstracts. The mostdominant type of translation techniques was established equivalent due to thetranslator intention to avoid misunderstanding by using the dictionaries andparticular equivalent known by target language. It is recommended that in doingany translation, the most essential thing is to keep the meaning or the message ofthe source language remains the same when it is being translated into the targetlanguage.